Объяснение:
1) это биквадратное уравнение
9x^4-24x^2+6=0
x₁₋₄=±√[(24±√(24²-4*9*6))/18]=±√[(24±√360))/18]=
=±√[(24±6√10))/18]=±√[(4±√10))/3]
x₁=√[(4+√10))/3]
x₂=√[(4-√10))/3]
x₃=-√[(4+√10))/3]
x₄=-√[(4-√10))/3]
2)4x^3+4-6x^2-6x=0
4(x³+1)-6x(x+1)=0
2(x³+1)-3x(x+1)=0
2(x+1)(x²-x+1)-3x(x+1)=0
(x+1)(2x²-2x+2-3x)=0
(x+1)(2x²-5x+2)=0
1) x+1=0 ; x₁=-1
2) 2x²-5x+2=0
x₂₋₃=(5±√(25-16))/4=(5±3)/4
x₂=0,5
x₃=2
x₁=-1 ; x₂=0,5 ; x₃=2
Объяснение:
1) это биквадратное уравнение
9x^4-24x^2+6=0
x₁₋₄=±√[(24±√(24²-4*9*6))/18]=±√[(24±√360))/18]=
=±√[(24±6√10))/18]=±√[(4±√10))/3]
x₁=√[(4+√10))/3]
x₂=√[(4-√10))/3]
x₃=-√[(4+√10))/3]
x₄=-√[(4-√10))/3]
2)4x^3+4-6x^2-6x=0
4(x³+1)-6x(x+1)=0
2(x³+1)-3x(x+1)=0
2(x+1)(x²-x+1)-3x(x+1)=0
(x+1)(2x²-2x+2-3x)=0
(x+1)(2x²-5x+2)=0
1) x+1=0 ; x₁=-1
2) 2x²-5x+2=0
x₂₋₃=(5±√(25-16))/4=(5±3)/4
x₂=0,5
x₃=2
x₁=-1 ; x₂=0,5 ; x₃=2